Callosotomía posterior: un nuevo abordaje en Cirugía de Epilepsia - Sánchez González, Federico; Yasuda, Ezequiel; Rolón , Rafael; Iglesias, Brenda; Minghinelli , Federico; Martínez, Oscar (Revista Argentina de Neurocirugía, 2021)
Objective: to describe the new technique of posterior callosotomy applied to epilepsy surgery, including its indication, comparative advantages and results. Methods: two surgical cases are presented on video sequences, including patients with refractory epilepsy, with “drop attack” type seizures (loss of postural tone), presenting with recurring trauma and a potential life risk. Both patients, a 35 years-old woman and a 24 years-old man suffered from a congenital malformation of cortical development known as double cortex. One of the cases was operated in a semi-sitting position, trough a right parafalcine approach, and the other one in a prone position trough a left parafalcine approach. A 7cm parasagittal vertical incision, 2cm lateral to midline was performed, considering its upper limit at the union of the lambdoid and parasagittal suture, and its lower limit at the inion. A craniotomy of 4 by 4cm was performed, exposing the superior sagittal sinus. The venous regional anatomy allows an easy parieto-occipital lateral retraction. The callosotomy included the splenium and the body reaching anteriorly up to the region where we find both supplementary motor areas. Results: no postoperative complications were found. One case presented with a disconnection syndrome, resolving in 2 weeks. A 90% reduction of the seizure frequency was achieved, improving the quality of life and the degree of Independence of the patients. Conclusions: posterior callosotomy is a safe, less invasive and highly effective procedure against drop attack type seizures in refractory Epilepsy.